SASAK MUSLIMS AND INTERRELIGIOUS HARMONY: Ethnographic Study of the Perang Topat Festival in Lombok - Indonesia (State Islamic University (UIN) of Sunan Ampel Surabaya, 2017)
Ample local traditions serve as the catalysts that help build social integration within multicultural society. The social inclusion is developed when people from diverse ethnic and religious groups are deliberate to engage. The perang topat festival is a local tradition in Lombok, Indonesia, which includes two communities from different ethnicities and religions: Balinese-Hindus and Sasak-Muslims. The festival has been celebrated for years and has contributed significantly to maintaining harmony between various ethno-religious groups. This article is an ethnographic research report of the perang topat festival. The tradition has existed as a symbol of civic engagement between Muslims and Hindus. Nevertheless, Muslim puritans have recently criticized and banned Muslims’ participation in the perang topat festival. The Muslim puritans believe that integrating religious rituals with traditions is a bid’ah (heresy). On the other hand, Muslim proponents of perang topat justify it through the construction of symbolic meanings of the festival site, utensils, and rituals in accordance with Islamic concepts.